Development of A Model of Recovery Origin of Modification of Exercise Massage and Muscle Strength on Reducing Lactic Acid in Blood for Partner Football Players Surabaya - Fatkur Rohman Kafrawi; julianto; Fitria Hidayati (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2022)
Football is a high-intensity game of long duration, so in addition to technical, tactical, strategic and mental factors, there is one more determining factor, namely muscle fatigue, this factor which is often forgotten by coaches and players. The cause of player fatigue is due to heavy training or a tight competition schedule, there is a metabolic waste in the blood called lactic acid, this buildup of lactic acid causes fatigue but actually some of the lactic acid can be converted back into energy. The research objective to be achieved in this study was to determine the effect of exercise massage and muscle stretching in reducing lactic acid levels in the blood after a 45-minute round 1 soccer match. The type of research used is the type of research used is descriptive research. The population in this study, namely the population in this study were all football players in one team, namely 22 players from the Surabaya partner club. The data collection method used in this study is the measurement of blood lactic acid levels. The instrument used in this study was a blood lactic acid test using a blood lactic acid level measuring device. The data obtained will be analyzed using inferential statistics, namely the independent T test. Based on the results obtained, it can be concluded that the provision of sports massage and muscle stretching can reduce levels of lactic acid in the blood after the first half of the soccer match for 45 minutes. Based on the findings of the research on the first and second treatments, some suggestions are given, including; (1) for soccer players after training or matches, it is better to give sports massages and muscle stretching to maintain stamina in the next round, so that they can be maximized in training and matches; and (2) players who will be doing training or matches should stretch or warm up before being deployed to the field to avoid injury.